Migration patterns and adaptive strategies of indonesians /"Marore" in Southern Philippines a case study on the marores in Isulan, Sultan Kudarat - Estandarte, Karen Joy A.
This study provides a description of the migration patterns and adaptive strategies adopted by the Indonesian entrants in Southern Mindanao. It looks into the geographical scope and location with which this particular migration takes place and the factors influencing the migrants' decisions to move in Southern Philippines. The existence of family networks and social ties and other facilitators of migration (such as religious institution) are the major players in hastening the process of adaptation of the Indonesians or ?Marores?, whether as an individual or as a group. As an individual, their social adaptation is tied to their job and family. While as a group, external factors such as Indonesian Consulate General and religious institutions gain attention in this social process.
Thesis, Undergraduate (BA Social Science) -- U. P. in Mindanao